The potential of Islamic Pawn System: a study on the appropriateness on Muassasah Gadaian Islam Terengganu operation in Sabah - Mohd Zulkifli Muhammad; Hanudin Amin; Mohd Faisol Ibrahim; Mohd Fahmi Ghazali; Hazmi Dahlan (Universiti Malaysia Sabah, 2010)
Purpose - The need for an Islamic pawnshop has been discussed by the researchers within in Malaysia as well as other countries (for example: Nasifah, Nor Mariana & Nur Azura, 2005; Ismail & Sanusi, 2005; Ismail, 2004; Kon Lim, 2003; Ismail & Nur Zakiah, 1997; Rugayah, 1986). The Islamic based pawnshop transaction is still overlooked in Islamic finance practices and abandoned cases for the state government of Sabah. This issue is important as it might create a greater impact in promoting Islamic financial transactions among local people in the future. Therefore, the main purpose of this study is to understand public perceptions with regard to the need of Islamic pawnshop as this would help to improve the delivery of Islamic pawnshop facilities to Sabahan especially in terms of quality of services offered along with features and procedures of the products.